Peran R. Maladi dalam Penyelenggaraan Asian Games IV Tahun 1962 - Dina Kamelia Aribah; Sutiyah Sutiyah (Lembaga Yasin AlSys, 2026)
The hosting of the Fourth Asian Games in 1962 was not only an international sporting event but also part of the Indonesian government’s efforts to build the country’s image through Lighthouse Politics during the Soekarno administration. This study aimed to analyze R. Maladi’s role in organizing the Fourth Asian Games and its relationship with the implementation of Lighthouse Politics. The study employed the historical method, comprising topic selection, heuristics, source criticism, interpretation, and historiography. Primary sources included archives from the Arsip Nasional Republik Indonesia, presidential decrees, organizing committee documents, contemporary newspapers and magazines, and the official report of the Fourth Asian Games, supported by relevant secondary literature. The findings showed that R. Maladi’s experience as an athlete, Chair of the Persatuan Sepak Bola Seluruh Indonesia, broadcaster, and government official shaped his capacity to coordinate the organization of the Fourth Asian Games. His administrative role encompassed Indonesia’s bid to host the Games, the refinement of the organizational structure of the Dewan Asian Games Indonesia, interinstitutional communication, press relations, and coordination with the Asian Games Federation. Meanwhile, his technical role included infrastructure development, athlete development, the provision of service facilities, the conduct of dress rehearsals, and event coordination. The Fourth Asian Games, held from August 24 to September 4, 1962, demonstrated Indonesia’s capability as the host through orderly ceremonies, systematic scheduling, and Indonesia’s success in ranking second in the medal standings. This success strengthened Indonesia’s international image and supported Soekarno’s Lighthouse Politics, although the issues involving Taiwan and Israel resulted in diplomatic consequences. This study confirms that R. Maladi played a strategic role in integrating administrative, technical, sporting, and political interests, thereby making the Fourth Asian Games an instrument of diplomacy and a representation of Indonesia’s ambitions during the Guided Democracy era.